E08 Cerebral blood flow is associated with disease severity and cognitive defecits in pre/early huntington's disease. (September 2018) - Furby, Hannah; Ralph, James; Rosser, Anne E; O'Callaghan, Peter; Murphy, Kevin; Wise, Richard G; Steventon, Jessica J
Abstract : Background: Preclinical and post-mortem studies reveal cerebrovascular abnormalities in the HD brain. Arterial spin labelling (ASL) MRI can be used to non-invasively measure cerebral blood flow (CBF) in the HD brain, a factor known to reflect cerebrovascular health. Lower CBF has been reported in cortical and subcortical grey matter (GM) regions in early HD patients and reductions in CBF exceed changes in GM volume (Chen et al., 2012). Reduced CBF may contribute to neuronal dysfunction and cognitive performance. Alterations in CBF need to be probed earlier in the disease course. Aims: To assess early signs of cerebrovascular pathology in a pre-/early-symptomatic HD cohort, by measuring cerebral blood flow (CBF) using ASL MRI. Methods: 3T MRI was performed at Cardiff University Brain Research Imaging Centre (CUBRIC). Fourteen pre-/early-HD gene carriers and 19 matched control volunteers were recruited. ASL MRI was used to quantify CBF across global grey matter (GM) and subcortical regions (caudate, putamen, thalamus and hippocampus). GM volume was measured from T1 weighted anatomical scans. Cognitive tests included the SDMT, STROOP, Trailmaking, SCOLP, Forward digit span and verbal fluency tests. Results/outcome: CBF was lower in HD carriers than controls in the right thalamus and right caudate, but not across global GM (p<0.05). However, global GM and left thalamus CBF was related to disease burden score (Age x (CAG −35.5), where those later in the disease showed elevated CBF. Volume was significantly lower in HD carriers than controls in caudate, putamen and thalamus, but not the hippocampus. Regional volume did not predict CBF differences. Cognitive performance was generally lower in HD group, and bilateral caudate CBF predicted performance on SDMT and SCOLP tasks, but this effect was similar in both groups. Conclusions: Apparent alterations in CBF can be detected in pre-/early-HD. CBF was related to cognition, but not to GM volume. A CBF reduction in distinct subcortical regions suggest that early abnormalities are not global, and may first occur locally in key regions in HD. A disease related increase in CBF may reflect an early compensatory elevation in CBF. How CBF is related to HD pathology remains to be elucidated. Findings highlight the additional value of ASL MRI as a non-invasive measure of HD pathology that complements typical anatomical MRI approaches.